2021
DOI: 10.1111/1758-5899.12930
|View full text |Cite
|
Sign up to set email alerts
|

Beyond immigration: Moving from Western to Global Indexes of Migration Policy

Abstract: Over the last twenty years, researchers have undertaken systematic comparison of migration policy by creating sets of policy indicators/indexes at the national level. These indicators are designed to analyse the differences and trends in migration policy and then be used by the research community to assess the determinants and effects of policy. This article aims to assess the comprehensiveness of current migration policy indicators by analysing their thematic, geographical and temporal coverage as a way of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
(50 reference statements)
0
18
0
1
Order By: Relevance
“…In this short paper we presented the main findings of the MIPEX 2020, with a focus on naturalisation policies. Most indices addressing naturalisation policies focus on EU and Western countries (Solano & Huddleston, 2021a), while developing countries and emigration policies have been largely neglected. This trend follows a general bias in the wider field of migration studies, as shown by recent comprehensive reviews of the field (Levy, Pisarevskaya & Scholten, 2020;Pisarevskaya, Levy, Scholten & Jansen, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this short paper we presented the main findings of the MIPEX 2020, with a focus on naturalisation policies. Most indices addressing naturalisation policies focus on EU and Western countries (Solano & Huddleston, 2021a), while developing countries and emigration policies have been largely neglected. This trend follows a general bias in the wider field of migration studies, as shown by recent comprehensive reviews of the field (Levy, Pisarevskaya & Scholten, 2020;Pisarevskaya, Levy, Scholten & Jansen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of the comparative studies of citizenship and migration policies, Giacomo Solano and Thomas Huddleston (2021) note that the outstanding majority of the existing analyses concentrate on European and Western countries. With more than one third of immigrants worldwide settling in low or middle-income countries and three quarters of the refugee population living in African, Asian, Latin American and Caribbean states, this Westerncentric perspective is problematic.…”
Section: éMilien Fargues*mentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors contribute to the migratory flows and stocks (forced or voluntary) to destination countries, which have been extensively addressed in the literature (Dustmann & Preston, 2007 ; Pedersen et al, 2008 ; Simpson, 2017 ). We distinguish short-term migrants (seasonal agricultural workers, students, tourists, or temporary residents) and long-term migrants that include permanent residents, the first step on a path towards the creation of members, namely the citizenship (Goodman, 2019 ; Solano & Huddleston, 2021 ). Migration and migrant integration dynamics influence the number and characteristics of migrants entering a country, as well as the integration outcomes (Helbling & Leblang, 2019 ; Garcés-Mascare nas & Penninx, 2016 ; Czaika & De Haas, 2013 ; Massey et al, 1998 ) At the same time, the receiving society defines all the laws and policies that relate to the selection, admission, integration, settlement, and full membership of migrants in a country (Solano & Huddleston, 2021 ; Bjerre et al, 2015 ; Hammar, 1990 ).…”
Section: Theoretical Framework and Related Workmentioning
confidence: 99%
“…We distinguish short-term migrants (seasonal agricultural workers, students, tourists, or temporary residents) and long-term migrants that include permanent residents, the first step on a path towards the creation of members, namely the citizenship (Goodman, 2019 ; Solano & Huddleston, 2021 ). Migration and migrant integration dynamics influence the number and characteristics of migrants entering a country, as well as the integration outcomes (Helbling & Leblang, 2019 ; Garcés-Mascare nas & Penninx, 2016 ; Czaika & De Haas, 2013 ; Massey et al, 1998 ) At the same time, the receiving society defines all the laws and policies that relate to the selection, admission, integration, settlement, and full membership of migrants in a country (Solano & Huddleston, 2021 ; Bjerre et al, 2015 ; Hammar, 1990 ). Citizenship, migration, and integration policy, albeit in different ways, are distinct policy domains and creates the conditions that support or hinder migrants’ inclusion in the destination society.…”
Section: Theoretical Framework and Related Workmentioning
confidence: 99%